Altered immune signatures in breast cancer lymph nodes with metastases revealed by spatial proteome analyses - Oscar Briem; Balázs Tahin; Asger Meldgaard Frank; Lina Olsson; Anna Sandström Gerdtsson; Eva Källberg; Karin Leandersson (Journal of Translational Medicine)
Abstract Background Metastasis to lymph nodes is strongly associated with reduced survival in breast cancer patients. To increase the understanding on how lymph node metastasis impairs the local immune response in affected lymph nodes, we here studied spatial proteomic changes of critical lymph node immune populations in uninvolved lymph nodes (UnLN) and paired lymph nodes with metastases (LNM) from five breast cancer patients. Methods The proteome was analyzed for cortical lymphocyte compartments, subcapsular sinus (SCS) and medullary sinus (MS) CD169+ macrophages, using the Digital Spatial Profiling (DSP) platform from NanoString. Results Our results identified a stable proteome of SCS CD169+ macrophages in LNM, with the exception for downregulation of the anti-apoptotic protein Bcl-xL and FAPα, but a clear reduction in numbers of SCS CD169+ macrophages in LNM. In contrast, the proteome of MS CD169+ macrophages, B-cell compartments and interfollicular T-cells showed altered immune signatures in LNM, indicating that the decline in SCS CD169+ macrophages coincide with a malfunction in the local, anti-tumor immune responses. Conclusions The findings from our study support the notion that metastasis to lymph nodes in breast cancer patients modifies local immune responses. These changes may contribute to explain unsuccessful therapeutic responses, and thereby worsened prognosis, for breast cancer patients with LNM.